2019
DOI: 10.1007/s11579-019-00241-1
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio choice, portfolio liquidation, and portfolio transition under drift uncertainty

Abstract: This paper presents several models addressing optimal portfolio choice, optimal portfolio liquidation, and optimal portfolio transition issues, in which the expected returns of risky assets are unknown. Our approach is based on a coupling between Bayesian learning and dynamic programming techniques that leads to partial differential equations. It enables to recover the well-known results of Karatzas and Zhao in a framework à la Merton, but also to deal with cases where martingale methods are no longer availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…In their model, prices contain an unpredictable martingale component, and an independent stationary (visible) predictable component-the alpha component. Bismuth, Guéant and Pu (2016) study models in which the drift of the asset price process is a latent random variable in an optimal portfolio selection setting, for an investor who seeks to maximize a Constant Absolute Risk Aversion (CARA) and Constant Relative Risk Aversion (CRRA) objective function, as well as in the cases of optimal liquidation in an Almgren-Chriss like setting.…”
mentioning
confidence: 99%
“…In their model, prices contain an unpredictable martingale component, and an independent stationary (visible) predictable component-the alpha component. Bismuth, Guéant and Pu (2016) study models in which the drift of the asset price process is a latent random variable in an optimal portfolio selection setting, for an investor who seeks to maximize a Constant Absolute Risk Aversion (CARA) and Constant Relative Risk Aversion (CRRA) objective function, as well as in the cases of optimal liquidation in an Almgren-Chriss like setting.…”
mentioning
confidence: 99%
“…With the increase in α, investors will speed up the early liquidation speed and amount so as to obtain the maximum returns. From Figures 4,5,11,and 12, the change of b has the same effect on liquidation behaviour X t . When b gets larger, investors will liquidate faster so that they will reduce the risk of holding and get the maximum returns.…”
Section: Numerical Simulationmentioning
confidence: 78%
“…ey obtained the form of optimal liquidation behaviours by solving the HJB equation. Based on the Bayesian learning and dynamic programming techniques, Bismuth et al [11] researched the optimal portfolio choice, portfolio liquidation, and portfolio transition problems. rough the optimal control method, they found that the optimal behaviour is the solution of the HJB equation.…”
Section: Introductionmentioning
confidence: 99%
“…We choose a CARA utility function U pxq "´expp´pxq, with p ą 0. It has been shown in [5,Corollary 1] that the optimal portfolio Figure 3. Simulation of pY t q tPr0,T s using the (continuous-time) optimal strategy (Opt), the (Q) estimated one, and the Benchmark strategy (Bench) to solve the Portfolio Liquidation problem.…”
Section: Portfolio Selectionmentioning
confidence: 99%